Group Cognitive Behavior Therapy Reversed Insula Subregions Functional Connectivity in Asthmatic Patients - Zhang, Yuqun; Yang, Yuan; Bian, Rongrong; Yin, Yingying; Hou, Zhenghua; Yue, Yingying; Chen, Huanxin; Yuan, Yonggui (Frontiers in Aging Neuroscience, 2017)
Background: Group cognitive behavior therapy (GCBT) is an effective treatment in improving self-management behaviors and quality of life for asthmatic patients. However, the mechanisms by which GCBT improves asthma-related clinical symptoms remain unknown. Previous studies have indicated that insula is an important region involved in the neuropathology of asthma. Therefore, we examined the possible alteration of functional connectivity (FC) in insula subregions after GCBT in asthmatic patients. Methods: 42 asthmatic patients and 60 healthy controls (HCs) received resting-state functional magnetic resonance imaging (rs-fMRI) scan and clinical assessments, 17 asthmatic patients completed GCBT treatment consisting of 8 sessions, and then received rs-fMRI scan and clinical assessments. Results: Asthmatic patients had greater left ventral anterior insula (vAI) FC with the left cerebellum posterior lobe, right middle temporal gyrus and bilateral anterior cingulate cortex (ACC), but less FC with bilateral postcentral gyrus, bilateral occipital lobe and left precentral gyrus compared with HCs. FC between left posterior insula and left medial frontal gyrus also increased in the patients. In addition, right vAI showed increased FC with right caudate and left putamen. FC between right dorsal anterior insula (dAI) and left calcarine however decreased. The increase in FC in insula subregions were significantly improved following GCBT. FC between the left vAI connectivity and left postcentral gyrus was positively correlated with the percentage of improvement in 17-items Hamilton depression rating scale scores, and FC between the right dAI and left calcarine was negatively associated with the improvement percentage in asthma control test scores. Conclusions: This study in the first time demonstrated that GCBT led to significant improvement of FC between insula subregions and other brain regions.